1997
DOI: 10.1148/radiology.205.1.9314984
|View full text |Cite
|
Sign up to set email alerts
|

Basilar tip aneurysm: endovascular treatment with Guglielmi detachable coils--midterm results.

Abstract: Endovascular treatment of a basilar tip aneurysm with Guglielmi detachable coils seems to be a safe and less invasive alternative to surgical clipping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…14 Comparison with other published series of endovascular treatment not limited to the subset of ruptured posterior circulation lesions reveals comparable outcome statistics. 5,[13][14][15][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] These series (Table 2) show GOS I outcome in 44% to 100% of good-grade patients, with a mean of 79%.…”
Section: Clinical Outcomesmentioning
confidence: 92%
“…14 Comparison with other published series of endovascular treatment not limited to the subset of ruptured posterior circulation lesions reveals comparable outcome statistics. 5,[13][14][15][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] These series (Table 2) show GOS I outcome in 44% to 100% of good-grade patients, with a mean of 79%.…”
Section: Clinical Outcomesmentioning
confidence: 92%
“…25 Table 10 summarizes the data from six such studies. 1,15,22,27,32,34 In a systematic review of five published articles, Lozier and colleagues 25 collected data on the indications for endovascular therapy of 182 BA apex aneurysms. In 50.5% of the pa- (7) 7 (3) 0 (0) 0 (0) mild permanent deficit due to coil treatment 7 (7) 1 (0.5) 0 (0) 0 (0) severe permanent deficit due to coil treatment 3 (3) 6 (3) 0 (0) 2 (7) death due to coil treatment 2 (2) 5 (2) 0 (0) 0 (0) preexisting deficit 12 (11) 8 (4) 6 (32) 1 (3) mild permanent deficit independent of 8 (8) 7 (3) 2 (11) 0 (0) endovascular treatment severe permanent deficit independent of 4 (4) 28 (14) 1 (5) 2 (7) endovascular treatment death independent of endovascular treatment 1 (1) 13 (6) 0 (0) 0 (0) noncoil procedure-related severe permanent deficit 1 (1) 0 (0) 0 (0) 0 (0) * Clinical outcome data unavailable for three ruptured lesions.…”
Section: Endovascular Coil Occlusion Of Ba Tip Aneurysmsmentioning
confidence: 99%
“…5,8,10,12 Two of 6 studies reported the incidence of hydrocephalus (29 of 76 patients; 38.2%). 10,11 Only 1 study mentioned the occurrence of 2 medical complications (nonfatal pulmonary embolism and fatal renal failure). 9…”
Section: Baseline Characteristics: Basilar Apexmentioning
confidence: 99%
“…The most accessible data arose from articles that presented tables listing the baseline characteristics, initial and follow-up angiographic occlusion percentages, complications, and clinical outcome measures for individual patients. 2,10,11,18 Other studies provided tables, charts, or text descriptions of subsets of the cohort from which data were extracted with varying degrees of difficulty. 1,8,9,12,[15][16][17] Data regarding aneurysm occlusion on initial and postoperative angiograms were often presented in such a way that it was difficult or impossible to track the fate of an individual aneurysm.…”
Section: Data Accessibility and Data Qualitymentioning
confidence: 99%